BUSINESS ANALYSIS OF BROWN SUGAR INDUSTRY AND DEVELOPMENT STRATEGY WITH FISHBONE ANALYSIS OF HOUSEHOLD SKILLS IN PARANGGUPITO SUB DISTRICT WONOGIRI DISTRICT - Danang Setiaji (JURNAL ILMIAH AGRINECA, 2017)
This study aims to determine the cost of reception, acceptance, income and development strategy with the method of analysis fishbone on the business of sugar – scale households in Wonogiri Regency. The basic research used is a method the descriptive analysis. This study was conducted in the district Paranggupito district Wonogiri is centra brown sugar production in the district Wonogiri located in the southern extremity of the district Wonogiri directly borders with the ocean indonesia. The determination of the village samples done with purposive sampling that considering the village has unit effort industry brown sugar. The village elected is the village Gudangharjo dan the village Sambiharjo that manufacturer circulation in the district Paranggupito.A sample of respondents conducted in disproportionately as much as 30 people. The kind of and resources used data from primary data and data secondary. The techniques collecting data do with the interview, observations, and records begin. The result of research shows that the cost of a total of an average of the brown sugar scale of the household in the Wonogiri regency is Rp. 45.590,88 per day. The average revenue obtained amounted to Rp. 41.215 per day, so the average revenue obtained by Rp. – 4.375,88 per day, this happens because family labor is taken into account. Next to strategy of the development of the effort industry brown sugar by doing an increase in the knowledge of the workforce through training and guidance from the local goverment to improve the quality of brown sugar and expansion of the market into the marker modern and innovate in packaging through SOP that has been made by the grup that effort ndustry can be competing in the era of the enforcement of MEA.